MINERALISASI DAN POLA ALTERASI DAERAH LAKEA, KECAMATAN LAKEA KABUPATEN BUOL, PROVINSI SULAWESI TENGAH - Idarwati Idarwati (PROMINE, 2013)
The research area is located in the village of Lakea, Lakea subdistrict, Buol district, Central Sulawesi Province. Constituent Lithology within research area consists of three units, these are litodem lava basalt that mainly be composed by lava andesite and lava basalt which partly fractured, volcanic breccia, and tuff; Sandstone Unit mainly composed by sandstone, mudstone, muddy sandstone, and conglomerate; and the last unit is limestone as Coral Limestone Unit. Alteration assemblage is divided into four zones, namely argillic alteration zone (silicon oxide (kuarsa), magnesium aluminum iron silicate hydroxide, potassium aluminum silicate hydroxide dan sodium calcium aluminum silicate (albit), phyllic alteration zone (serisit/muskovit-kuarsa-klorit-feldspar), propylitic alteration zone (Chlorite-serpentine, Illite, Albite, calcian, ordered, Quartz, Muscovite ), and silicified alteration zone (quartz/silica + adularia + calcit± illite). The mineralization is controlled by open space filling with disseminated distribution. Gold mineralization usually associated with pyrite, chalcopyrite, and galena. Mineralization is found fill the major structural pattern with southeast-northwest direction. The fluid inclusion measurement results obtained that microthermometry Th (homogenization temperature when the fluid trapped in the crystals) ranged from 172 ~ 332 °C with a measurement range from 180.9 to 211.0 °C, and the melting temperature (first ice melting Temperatures / Tm) average ranges -1, 2 to 0.8 C. By calculations, the depth of the formation rate is 79.4 ~ 1712 m, and under pressure about 8.2 ~ 130.3 bar.